Recuperação funcional coxo-femoral pós-operatória em cães: estudo clínico e biomecânico. - Barbosa, Anna Laeticia da Trindade (2008)
The hip joint is the more frequently joint injured in dogs for external traumatism or degenerative diseases. Many studies have been accomplished in the evaluation of new surgical techniques, however little has been describing about evaluations in long period Recent works have been using the force platform at gait as objective method in association to the other parameters consecrated in the evaluation of new orthopedics techniques. However, there are no studies using the platform in pattern ortostático as in the human medicine, for support evaluation and weight transfer. The propose of this work was to standardize the use of the force platform in ortostatic pattern in dogs, to test it at surgical orthopedics patients and to evaluate the patients' recovery with hip diseases of surgical resolution through the parameters clinic, and force platform for static collection. For this clinical evaluation (lameness degrees, thigh circumference, radiografic exam) was accomplished and biomechanical evaluation through of the force plate for static collection of 21 operated dogs of the hip joint with diagnosis of traumatic hip luxation , fracture of head and femoral lap or aseptic necrosis of the femoral head and 6 healthy dogs without report of orthopedics problems. The platform in pattern ortostático an efficient and more sensitive objective parameter was shown than the others in some situations, being his/her appropriate use in the evaluation of orthopedic patient. This association to others parameters turned the evaluation of the appraised patients' recovery more completes and trustworthy. The recovery of the animals was very good, demonstrating that most is (approximately 70%) with function of the affected member practically reestablished, with some individual variations, been their recovery classified between excellent and very good. The animals that presented recovery classification of reasonable to bad, didn't possess enough time for recovery, they presented complications or they had the late recovery due to the obesity. This way, it is concluded to be very good the prognostic in long period of these affections with surgical treatment through transacetabular pinning insertion and arthroplasty excision of the femoral head; and that the evaluation of animals recovery for clinic and biomechanical (in study pattern ortostático) is practice and efficient.